Ultralong floating hydrogel raft for prolonged gastric retention - Kwang, Guo Dong (2023)
The optimal therapeutic efficiency of any treatment depends on patient adherence to the medication regimen. Medication adherence is the cornerstone of treatment outcomes that may consequently impact economic and healthcare costs. With the oral route being the preferred route of drug administration, slow or extended-release oral formulations can, therefore, be utilized. Here, a biocompatible oral delivery system that can be retained in the stomach for a week, while providing continuous release of the encased drug, is proposed. The fabrication of the delivery system was achieved using a simple mold casting technique. The hydrogel-based raft was able to float under simulated gastric conditions for seven days with pH switches to mimic the fasted and fed states of the stomach. The functionality of such a delivery system has been exemplified using two different model drugs—risperidone and metoprolol tartrate of varied solubilities and has been shown to effectively sustain the release of drugs under the tested conditions.